Exploring the Dynamics of Umbrella Brand and House of Brand Strategies on Organizational Performance: A Comparative Analysis - AJAYI, OLALEKAN EZEKIEL (ASEAN Marketing Journal, 2024)
The study examined the impact of dimensions of Umbrella Brand and House of Brand Strategies (brand awareness, customer trust, Brand Message, and Brand decision) on Organizational Performance. A sample of 109 Marketing managers and representatives within the Coca-Cola Company in Ido, Lagos Mainland. Data analyse both descriptive and inferential statistics using the IBM-SPSS version 27. There was significant prediction of brand awareness on organizational performance F(1, 99) = 302.14, R2 = 0.46; pcustomer trust on organizational performance F(1, 99) = 102.24, R2 = 0.46; pbrand awareness on organizational performance F(1, 99) = 88.15, R2 = 0.38; pbrand decision on organizational performance F(1, 99) = 78.01, R2 = 0.27; pbrand decision on organizational performance F(1, 99) = 110.01, R2 = 0.48; p<.05).The study concluded that brand awareness, customer trust, Brand Message, and Brand decision predicted organizational performance. The study recommend that management should put up interventions that can help improve umbrella Brand and House of Brand and its dimension in a bid to have an effective organizational performance.